Interfacial Engineering for Improved Photocatalysis in a Charge Storing 2D Carbon Nitride: Melamine Functionalized Poly(heptazine imide). Issue 6 (21st December 2020) - Kröger, Julia; Jiménez‐Solano, Alberto; Savasci, Gökcen; Rovó, Petra; Moudrakovski, Igor; Küster, Kathrin; Schlomberg, Hendrik; Vignolo‐González, Hugo A.; Duppel, Viola; Grunenberg, Lars; Dayan, Cem B.; Sitti, Metin; et al.
Abstract: Carbon nitrides constitute a class of earth‐abundant polymeric semiconductors, which have high potential for tunability on a molecular level, despite their high chemical and thermal inertness. Here the first postsynthetic modification of the 2D carbon nitride poly(heptazine imide) (PHI) is reported, which is decorated with terminal melamine (Mel) moieties by a functional group interconversion. The covalent attachment of this group is verified based with a suite of spectroscopic and microscopic techniques supported by quantum–chemical calculations. Using triethanolamine as a sacrificial electron donor, Mel‐PHI outperforms most other carbon nitrides in terms of hydrogen evolution rate (5570 µmol h −1 g −1 ), while maintaining the intrinsic light storing properties of PHI. The origin of the observed superior photocatalytic performance is traced back to a modified surface electronic structure and enhanced interfacial interactions with the amphiphile triethanolamine, which imparts improved colloidal stability to the catalyst particles especially in contrast to methanol used as donor. However, this high activity can be limited by oxidation products of donor reversibly building up at the surface, thus blocking active centers. The findings lay out the importance of surface functionalization to engineer the catalyst–solution interface, an underappreciated tuning parameter in photocatalytic reaction design. Abstract : Addressing a bottleneck in photocatalysis: Covalent surface modifications of the 2D carbon nitride poly(heptazine imide) with melamine groups strongly influence its polarity and photo(electrochemical) properties. This potent tuning pathway also results in the boosting of the photocatalytic hydrogen evolution due to increased donor interactions and enhanced hole extraction.